Divergent Human Papillomavirus Associated with Recurrent Respiratory Papillomatosis with Lung Involvement - Yuan, Hang (American Society for Microbiology, 2013)
A divergent human papillomavirus (HPV), isolated from a lung lesion of a patient with recurrent respiratory papillomatosis, was fully cloned, sequenced, and genetically characterized. DNA analysis revealed that the HPV contained a 10.4-kb genome, with a duplication of 2,493 bp that includes partial L1-long control region (LCR)-E6-E7-partial E1 sequences.